Study on Abnormal Transmission of Date Frames Based on PT-CAN Bus - Wen Fang; Chunhua Zhang; Yangyang Li; Baopeng Zhao (Journal of Advanced Transportation)
To research the problem of abnormal transmission, experiments were conducted under the conditions of the BMW F18 model. The real-time signal mutation value of PT-CAN was measured by the IBIM synthetic testing box, and the cause of abnormal transmission on the data bus was identified by the value of the signal mutation. Experiments compared and analyzed the signal waveform of PT-CAN under the conditions of normal data transmission, CAN_H to ground loaded with different resistance, CAN_H to battery loaded with different resistance, CAN_L to ground loaded with different resistance, CAN_L to battery loaded with different resistance, between CAN_H and L loaded with different resistance, when CAN_H or L was disconnected, and when CAN_H and L were interchanged. Experimental results indicate that abnormal data transmission may cause abnormal signal waveform of PT-CAN bus, and the different PT-CAN signal clutter has certain different forms and reasons. Experimental results were effective for the identification of abnormal data transmission.